DAYLIGHT INVESTIGATION IN CAMPUS LECTURE THEATERS. CASE STUDY: SOUTH WEST COAST UNIVERSITY OF NIGERIA - OYELEYE OLAYINKA; MAKANJU TOLULOPE (Journal of Engineering Studies and Research)
Appropriate day lighting design saves lighting power energy (LPE) and reduces LPE cost. This research investigates daylight contribution of in selected north campus lecture theaters in a South West Coast University of Nigeria. TES 1332A lux meter was used for lux level determination. The window area to wall area (AWD to AW) ratio was determined using reliable algorithms. In the three studied buildings, the daylight contribution varies from 12 lux to 3803 lux; AWD to AW varies from 14 % to 22 % to 37 %; 22 % AWD to AW is considered moderate while 37 % AWD to AW is considered more suitable in the studied buildings.